The Influence of E-Wom and Social Media on Interest in Buying Camping in Bedugul and Lifestyle as a Mediation Variable - DEWI, Dewa Ayu Dwi Sukma; ADINEGARA, Gusti Ngurah Joko; JUNAEDI, I Wayan Ruspendi; KOMALASARI, Yeyen (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose: This research aims to increase our understanding of how people behave when they choose several camps in Bedugul. By knowing the factors that influence consumers' lifestyle and buying interest, camp managers in Bedugul can increase their presence on Social Media to attract consumers' buying interest. Methodology:This research uses quantitative methods with a descriptive approach. The research method uses the Structural Equation Model (SEM). Data collection was carried out by studying literature and distributing questionnaires to respondents. Data processing was carried out using IBM software called Smart-PLS version 3.0. The Slovin formula was used to determine the sample size. Findings:E-WOM has a positive and significant influence on lifestyle and interest in buying camping in Bedugul, Social Media has a positive and significant influence on lifestyle and interest in buying camping in Bedugul, lifestyle has a positive and significant influence on interest in buying camping in Bedugul, E-WOM and social media has a positive and significant influence on interest in buying camping in Bedugul through lifestyle as a mediating variable. Implication:This research was conducted on a small scale in the Bedugul area with limited coverage, so the results may not fully represent the wider situation. In order to gain a more comprehensive understanding and stronger generalizations, further research is needed on a larger scale and involving more variables. This will help in identifying and understanding various other aspects that may influence consumer buying interest in a broader context.